Learning styles and strategies of D/deaf and hard of hearing students in foreign language acquisition–a research report - Olszak, Izabela; Borowicz, Aleksandra (Frontiers in Education, 2025)
This article is dedicated to analyzing the learning styles, strategies, and ways of overcoming challenges in foreign language acquisition by D/deaf and hard-of-hearing students (DHH students). The ability of individuals with hearing impairments to acquire a foreign language effectively depends on various factors, such as the degree of hearing loss, the age at which language learning begins, and the availability of educational and environmental support. In research on this category of students, understanding specific learning styles and strategies that aid in the process of acquiring a new language is crucial. The article discusses diverse learning styles and strategies, as well as approaches to overcome difficulties preferred by D/deaf and hard-of-hearing individuals during foreign language learning. The quantitative study also examines educational strategies that support the development of language competencies in this group, including multimedia techniques, imagery, and visualizations that enhance and facilitate reading comprehension. The study aimed to identify dominant teaching styles and learning strategies for English among 55 DHH students from grades VII and VIII in selected primary schools. These schools follow the Core Curriculum for General Education, adapted for students with hearing impairments. A quantitative questionnaire was used, comprising three thematic sections on reading comprehension and learning difficulties. Participants answered closed questions using a three-point scale: I never do, sometimes do, always do. The key research questions explored: (1) The reading strategies DHH students use for comprehension; (2) Differences in strategy application based on gender, hearing loss degree, communication method, and onset time of hearing loss, (3) General difficulties DHH students face in learning foreign languages. The findings of a questionnaire were subjected to statistical analysis and indicate that appropriate adaptation of teaching methods and consideration of the individual preferences of deaf students can significantly improve their success in foreign language learning and their motivation to study.